Surgical treatment of newborns with coarctation of aorta and severe distal aortic arch hypoplasia by modified Amato method - Lekan, R. Y.; Buzovskyi, V. P.; Buriachenko, I. E.; Bosenko, V. I.; Lekan, I. R.; Popsuiko, O. V.; Tomak, A. I.; Rudometkin, O. V. (Journal of Education, Health and Sport, 2018)
Objective: The purpose of this study is to evaluate the effectiveness of surgical treatment of newborns with coarctation of the aorta and severe hypoplasia of the distal aortic arch in a modified Amato method according to the data of the immediate and mid-term results. Methods: 33 newborns with coarctation of aorta and severe distal aortic arch hypoplasia were subjected through left posterior thoracotomy using for plasty of arch tissue the left carotid artery and the left subclavian artery and then classic resection coarctation next extended end-to-end anastomosis.. Eight of them had associated difficult concomitant cardiac abnormality of large overload blood and associated of high pulmonary hypertension required pulmonary artery banding before distal aortic arch plasty and extended end-to-end anastomosis. Mean age and weight were 9 (6-21) days and 3,4 (2,5-3,9) kg, respectively. Median preoperative Z-score of distal aortic arch was - 3,26 (-4,56 to -2,12) and istmus -3,66 (-5,16 to -2,76). Results: Thirty one patients had successfully operated by this approach. The non- ischemic and ischemic aortic cross clamping mean time were 28 min and 25 min accordingly. The immediate postoperative mean Z-score of the distal aortic arch was 0.58, and after the average mid-term period of 4.7 (1-9) years it was – 0.17 (-0.36 to 0.75), which allows it to be affirmed these indicators as normal. Conclusions: Tissues the left carotid artery and the left subclavian artery after plasty give growth to distal arch of aorta in the mid-term period more than 93,9% of cases.